Analysis of Grammar and Morphology Teaching within the Arabic Language Program at an Islamic University of Riau in Indonesia | Tahliq Ta'lim al-Nahw wa al-Sarf fi 'Amaliyyat al-Tadris fi Qism Ta'lim al-Lughah al-'Arabiyyah bi al-Jami'ah al-Islamiyyah al-Riyawiyyah bi Indonesia - Akzam, Ismail; Zubaidah, Zubaidah (Institut Agama Islam Negeri Palangka Raya, 2024)
The gap in research regarding the integration of grammar and morphology in modern Arabic language education curricula in Indonesia has prompted this study. This research aims to analyze the teaching of nahwu and sharaf in the instructional process of students in the Arabic Language Education Department at Islamic University of Riau in Indonesia, employing a sequential explanatory approach. The methodology includes observations, interviews, and document analysis. The findings reveal a shift in the curriculum from a separate traditional system to an integrated approach, highlighting essential components for effective Arabic language teaching, the importance of integrated language skills, and the advantages of technology-based automated assessment for monitoring student progress. The implications suggest that effective teaching of nahwu and sharaf requires a comprehensive approach that combines various language teaching components and leverages technology for assessment and progress tracking. This research contributes to the development of more effective and integrated Arabic language teaching strategies at the higher education level in Indonesia.